miR-10-5p mediated susceptibility to chlorantraniliprole by targeting for SfGSTe1 in Spodoptera frugiperda (Smith) - Fan-Bin Kong; Ling-Ling Cui; Bai-Zhong Zhang; Yu-Tai Jiang; Yong-Po Lv; Pei Zhang; Yu-Yang Peng; Yun-Shan Xiong; Xiang Ji; Run-Qiang Liu (Scientific Reports)
Abstract Glutathione S-transferases (GST) in pests plays a critical role in insecticide resistance. In this study, SfGSTe1 expression significant upregulation under chlorantraniliprole exposure, chlorantraniliprole susceptibility improvement after injected dsSfGSTe1 and miR-10-5p target located in the 3′ UTR of SfGSTe1 conducted by luciferase reporter assays were observed in Spodoptera frugiperda (Smith). Injected miR-10-5p agomir reduced significantly SfGSTe1 abundance, together with increased chlorantraniliprole susceptibility, while injected miR-10-5p antagomir improved significantly SfGSTe1 abundance and thus decreased chlorantraniliprole susceptibility in the larvae of S. frugiperda. We revealed that the mRNA stability of SfGSTe1 by preventing its degradation that could have been induced by miR-10-5p and thus increased the resistance of S. frugiperda to chlorantraniliprole. This finding would help to study the mechanism of miRNAs in mediating insecticide susceptibility in pests.